On the Cauchy problem for a nonlinear variational wave equation with degenerate initial data. (November 2018) - Hu, Yanbo; Wang, Guodong
Abstract: This paper is focused on a one-dimensional nonlinear variational wave equation which is the Euler–Lagrange equations of a variational principle arising in the theory of nematic liquid crystals and a few other physical contexts. We establish the local existence and uniqueness of classical solutions to its Cauchy problem with initial data given on the parabolic degenerating line.